2019
DOI: 10.1038/s41598-019-52954-4
|View full text |Cite
|
Sign up to set email alerts
|

DeepIso: A Deep Learning Model for Peptide Feature Detection from LC-MS map

Abstract: Liquid chromatography with tandem mass spectrometry (LC-MS/MS) based quantitative proteomics provides the relative different protein abundance in healthy and disease-afflicted patients, which offers the information for molecular interactions, signaling pathways, and biomarker identification to serve the drug discovery and clinical research. Typical analysis workflow begins with the peptide feature detection and intensity calculation from LC-MS map. We are the first to propose a deep learning based model, DeepI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 36 publications
0
42
0
Order By: Relevance
“…DeepIso consists of two different deep learning-based components, which can learn multiple levels of the high-dimensional data itself represented by multiple layers of neurons and can be adapted to new situations. The peptide characteristics list investigated with this model matches with 97.43% of high quality MS/MS identifications in a standard dataset (Zohora et al, 2019). The third one is DeepNovo-DIA, de novo peptide sequencing Independent data acquisition (DIA) method of mass spectrometry data.…”
Section: Analysis Of Lc-ms/ms Data Sets Of Mhc-i and Mhc-ii Loaded Peptidesmentioning
confidence: 99%
“…DeepIso consists of two different deep learning-based components, which can learn multiple levels of the high-dimensional data itself represented by multiple layers of neurons and can be adapted to new situations. The peptide characteristics list investigated with this model matches with 97.43% of high quality MS/MS identifications in a standard dataset (Zohora et al, 2019). The third one is DeepNovo-DIA, de novo peptide sequencing Independent data acquisition (DIA) method of mass spectrometry data.…”
Section: Analysis Of Lc-ms/ms Data Sets Of Mhc-i and Mhc-ii Loaded Peptidesmentioning
confidence: 99%
“…These encouraging reports lead us to propose an exciting vision of a potential path forward for DIA data analysis, which is to discard even more levels of manual intervention, and to create a method that can allow for direct operation on the raw LC/MS‐MS maps. One research group has shown some applications for this way forward for the purposes of isotopic pattern detection in DDA data analysis and DIA de novo sequencing; DeepISO [ 21 ] and DeepNovo‐DIA [ 22 ] both operate directly on data from the LC/MS‐MS feature maps for their respective tasks. Although these methods still require a degree of pre‐ and post‐processing, they show that it is possible to automate increasingly large portions of the workflow that previously required large amounts of human expertise and prior knowledge.…”
Section: Automation Of Dia Analysismentioning
confidence: 99%
“…The success of deep learning (DL)-based methods, often replacing state-of-the-art classical model-based methods, in many fields such as medical imaging [17], biomedicine [18], and healthcare [19], has also encouraged the use of DL models for LC-MS proteomics analysis. To name a few, DeepIso [20] that combines a convolutional neural network (CNN) with a recurrent neural network (RNN) to detect peptide features; DeepNovo [21] and DeepNovo-DIA [22], which use DL-based approach (CNN coupled with RNN) for peptide sequencing on data-dependent acquisition (tandem-mass spectra) and data-independent acquisition MS data, respectively; pDeep [23] that adapt the bidirectional long short term memory for the spectrum prediction of peptides; and DeepRT [24] that employs a capsule network to predict RT by learning features of embedded amino acids in peptides. Despite the current successful DL approaches on analyzing LC-MS proteomics, most of the studies are empirically driven, and having a justifiable interpretation foundation is largely missing [25].…”
Section: Introductionmentioning
confidence: 99%